Tapping the Full Potential? Jumping Performance of Volleyball Athletes in Game-Like Situations - Fleddermann, Marie-Therese; Zentgraf, Karen (Frontiers in Psychology, 2018)
Background: One key issue in elite interactive team sports is the simultaneous execution of motor actions (e.g., dribbling a ball) and perceptual-cognitive tasks (e.g. visually scanning the environment for action choices). In Volleyball, one typical situation is to prepare and execute maximal block jumps after multiple-options decision-making and concurrent visual tracking of the ongoing game dynamics to find an optimal blocking location. Based on resource-related dual-and multi-tasking theories simultaneous execution of visual-cognitive and motor tasks may interfere with each other. Therefore, the aim of this study was to investigate whether volleyball-specific perceptual-cognitive demands (i.e., divided attention, decision making) affect blocking performance (i.e., jumping performance and length of the first step after the ready-block-position) compared to relatively isolated jumping performance. Methods: 22 elite volleyball players (1st – 3rd German league) performed block jumps in front of a net construction in a single-task condition (ST) and in two perceptual(-cognitive) dual-task conditions including a dual-task low (DT_L; presenting a picture of an opponent attack on a screen) and a dual-task high condition (DT_H; presenting videos of an offensive volleyball set play with a two-alternative choice). Results: The results of repeated-measures ANOVAs showed a significant effect of conditions on jumping performance (F(2, 42) = 33.64, p < .001, η²p = .62) and on the length of the first step after the ready-block-position (F(2, 42) = 7.90, p = .001, η²p = .27). Post-hoc comparisons showed that jumping performance in DT_H (p < .001) and DT_L (p < .001) was significantly lower than in ST. Also, length of the first step after the ready-block-position in DT_H (p = .005) and DT_L (p = .028) was significantly shorter than in ST. Conclusions: Our findings suggest that blocking performance (i.e., jumping height, length of the first step) decreases in elite volleyball players when a perceptual(-cognitive) load is added. Based on the theory of Wickens (2002), this suggests a resource overlap between visual-processing demands for motor performance and for tracking the dynamics of the game. Interference with the consequence of dual-task related performance costs can therefore also be found in elite athletes in their specific motor expert domain.